P.011 OnabotulinumtoxinA, quality of life, health resource utilization, and work productivity in chronic migraine: interim results from PREDICT. (5th June 2019) - Boudreau, G; Becker, WJ; Graboski, C; Ong-Lam, M; Finkelstein, I; Christie, S; Bhogal, M; Davidovic, G
Abstract : Background: We assessed long-term health-related quality of life (HRQoL) and functioning in adults receiving onabotulinumtoxinA for CM.Methods: Interim analysis of multicentre, prospective, observational study in adults naïve to botulinum toxin (NCT02502123). Mean change from baseline in Migraine-Specific Quality of Life (MSQ) score (primary); healthcare resource utilization (HRU) and work productivity (secondary) assessed in patients receiving 4 of 7 onabotulinumtoxinA treatments (Tx4; ~10 months).Results: Across treatments (baseline, n=196, post-Tx2, n=173, post-Tx4, n=137), the mean (SD) between-session interval and onabotulinumtoxinA dose was 13.1 weeks and 170.4 (17.2) U, respectively. MSQ scores increased significantly (P<0.0001) (baseline to post-Tx4; all role function domains). Patient percentages declined from baseline to post-Tx2 and post-Tx4 for emergency room visits (17.3%; 9.3%; 6.6%), hospital admissions (3.6%; 2.9%; 1.5%), and headache-related diagnostic testing (35.9%; 15.9%; 8.1%). The percentages of patients employed at baseline (73.5%) and post-Tx4 (72.3%) were similar. Hours worked increased slightly from baseline to post-Tx4 (28.0 [SD=15.4]; 29.4 [SD=16.0]). Headache-related missed work hours decreased (5.9 [SD=9.5]; 2.5 [SD=5.9]). Patients reported less headache-related impact on work productivity from baseline to post-Tx4 (5.4 [SD=2.1] vs 3.9 [SD=2.6]) and ability to perform daily activities (6.1 [SD=2.1] vs 4.2 [SD=2.8]).Conclusions: OnabotulinumtoxinA for CM improved HRQoL and work productivity and reduced HRU.